2022
DOI: 10.3389/fmars.2022.864344
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Responses of a Large, Benthic Elasmobranch to Catch-and-Release Angling

Abstract: Catch-and-release angling is widespread, but the impacts of this practice for captured individuals are understudied, especially among elasmobranchs. Studies on sub-lethal behavioural impacts are particularly sparse, despite their importance for the interpretation of biologging data and for assessments of species’ tolerance to capture. In this study, the behavioural responses of flapper skate (Dipturus intermedius) to catch-and-release angling were described for the first time, using archival observations (dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This assumption is consistent with skate morphology and diet studies of the common skate species complex ( D. batis ), which includes flapper skate and the common blue skate ( D. batis ) 45 , that have revealed the exploitation of a wide range of benthic prey 46 – 48 . The way that flapper skate ‘dig’ into the sediment when hooked by recreational anglers also demonstrates benthic movements 40 . Moreover, recent research has shown that it is possible to reconstruct movement trajectories for flapper skate under the assumption that they remain near to the seabed (Lavender et al, in prep).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This assumption is consistent with skate morphology and diet studies of the common skate species complex ( D. batis ), which includes flapper skate and the common blue skate ( D. batis ) 45 , that have revealed the exploitation of a wide range of benthic prey 46 – 48 . The way that flapper skate ‘dig’ into the sediment when hooked by recreational anglers also demonstrates benthic movements 40 . Moreover, recent research has shown that it is possible to reconstruct movement trajectories for flapper skate under the assumption that they remain near to the seabed (Lavender et al, in prep).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature-depth profiles recorded during recreational angling events by tagged individuals that were pulled to the surface were used to validate modelled temperature-depth profiles. Angling events were identified in the mark-recapture database maintained by NatureScot, Marine Scotland Science and the Scottish Association for Marine Science 40 (see Supplementary Information Sect. 4.1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second stage, a particle filtering (PF) process is used to incorporate movement. Alongside the central framework, the coupling of the AC‐branch and PF‐branch algorithms collectively represents a new family of algorithms for inferring movements and patterns of space use termed the ‘flapper family’, following its motivation by research on the Critically Endangered flapper skate ( Dipturus intermedius ) (Dodd et al, 2022; Lavender et al, 2021a, 2021b; Lavender, Aleynik, Dodd, Illian, James, Smout, et al, 2022; Lavender, Aleynik, Dodd, Illian, James, Wright, et al, 2022; Thorburn et al, 2021). To support algorithm application, we introduce the flapper R package.…”
Section: Introductionmentioning
confidence: 99%